2022
DOI: 10.35232/estudamhsd.1037317
|View full text |Cite
|
Sign up to set email alerts
|

Bi̇r Üni̇versi̇te Hastanesi̇ Sağlik Çalişanlarinda Mesleki̇ İyoni̇ze Radyasyon Maruzi̇yeti̇ne Bağli Sağlik Yakinmalari

Abstract: ÖzetRadyasyon, doğada daima var olan ve canlı sistemleri etkileyen fiziksel bir faktördür. Bu çalışmada; iyonize radyasyon kaynaklarıyla çalışan sağlık çalışanlarında dozimetre ve kişisel koruyucu donanım kullanım sıklıklarının belirlenmesi, mesleki iyonize radyasyon maruziyetine bağlı olduğu düşünülen sağlık yakınmalarının iyonize radyasyon maruziyeti olan ve olmayan gruplarda karşılaştırılması amaçlanmıştır. Tanımlayıcı epidemiyolojik araştırma, 4 Ağustos-30 Kasım 2020 ve 2 Mayıs-30 Haziran 2021 tarihleri ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“…The age group of more than half of the nurses was in the range of 31-45 years, the majority were female, had a bachelor's degree, and had more than 15 years of professional experience. The results of many studies on healthcare workers were similar to this study in terms of age groups and gender, and ERcp nurses were found to have more professional experience (ardıç & S ¸ahin, 2022;avcı, 2016;chu, 2022;Gül, andsoy, Görücü, & Özen, 2019;hirvonen et al, 2019). The fact that more than half of the participants in the study were smokers is an important finding.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The age group of more than half of the nurses was in the range of 31-45 years, the majority were female, had a bachelor's degree, and had more than 15 years of professional experience. The results of many studies on healthcare workers were similar to this study in terms of age groups and gender, and ERcp nurses were found to have more professional experience (ardıç & S ¸ahin, 2022;avcı, 2016;chu, 2022;Gül, andsoy, Görücü, & Özen, 2019;hirvonen et al, 2019). The fact that more than half of the participants in the study were smokers is an important finding.…”
Section: Discussionsupporting
confidence: 83%
“…protective equipment and comply with radiation safety during the procedure (Thambura & Vinette, 2019). in this study, all nurses took precautions to protect themselves from radiation during the ERcp procedure and mostly used lead aprons, thyroid protectors, and lead glasses, and this was similar to the literature (alshabi et al, 2022;ardıç & S ¸ahin, 2022;avcı, 2016;Gül et al, 2019;Vural et al, 2012).…”
Section: (Continued)supporting
confidence: 54%
See 1 more Smart Citation
“…sources and cosmic rays, 20% from artificial sources. 1 In cells exposed to ionizing radiation, DNA single-or double-strand breaks, oxidative damage, or DNA protein cross-linking damage can occur. 2,3 The biological response to radiation varies depending on the radiation dose, type, characteristics of the affected cell, and type of DNA damage.…”
mentioning
confidence: 99%
“…4 Most artificial ionizing radiation sources are radiation sources used in medicine for diagnosis and treatment. 1 Hospital staff working in areas such as radiology, nuclear medicine, and radiation oncology are occupationally exposed to ionizing radiation. The working conditions of personnel in radiation-exposed departments are determined by the regulations and guidelines of international agencies such as the International Atomic Energy Agency, the International Commission on Radiological Protection, and national protocols.…”
mentioning
confidence: 99%